Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1111/j.1432-1033.1979.tb13166.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of 3‐Oxo‐acyl Groups in the 6,6′‐Diesters of α‐d‐Trehalose

Abstract: The 'cord factor' from Corynebacterium diphtheriae was fractionated by thin-layer chromatography of the trimethylsilyl derivatives into three main components: the true 'cord factor' B1 which has been described previously and two compounds, B2 and B3, containing 3-0x0-acyl esters. These products were analyzed by mass spectrometry (field desorption/cationization and electron impact of the trimethylsilyl derivatives) and by chemical degradation.Compound B3 is a 6,6'-bis(3-oxo-acyl)-cc-~-trehalose. The 3-0x0-acyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…180±182 These workers reported that the dehydro product was in the form of an ester of trehalose but trehalose does not appear to be required for, nor is it stimulatory to, the cell-free activity 180,183,184 and such esters of the dehydrocorynomycolate are rapidly degraded back to palmitic acid. 185 The nature of the carrier immediately following the condensation remains unclear. Datta and Takayama characterized a phospholipid which contained dehydrocorynomycolate from large-scale cell-free incubations but were unable to conclusively identify this material.…”
Section: The Condensation and Carriersmentioning
confidence: 99%
“…180±182 These workers reported that the dehydro product was in the form of an ester of trehalose but trehalose does not appear to be required for, nor is it stimulatory to, the cell-free activity 180,183,184 and such esters of the dehydrocorynomycolate are rapidly degraded back to palmitic acid. 185 The nature of the carrier immediately following the condensation remains unclear. Datta and Takayama characterized a phospholipid which contained dehydrocorynomycolate from large-scale cell-free incubations but were unable to conclusively identify this material.…”
Section: The Condensation and Carriersmentioning
confidence: 99%
“…The mycobacterial Pks13 enzyme was shown to be able to use these short substrates in a recombinant Corynebacterium strain to synthesize mycolic acids in vivo . Published data have suggested that a,a-D-trehalose or D-glucose play a role in the biosynthesis of mycolic acids (Promé et al, 1974;Puzo et al, 1979;Shimakata et al, 1986), and a more recent report has shown the requirement of trehalose (Tropis et al, 2005). In order to seek for their potential involvement during the condensation reaction catalyzed by Pks13, assays supplemented with these sugars were realized.…”
Section: Pks13 Generates Polyol Derivativesmentioning
confidence: 99%
“…AKA: a-alkyl b-ketoacid. Note that spot b was identified as (a-myristyl b-ketopalmitoyl),palmitoyl trehalose by MALDI-TOF MS (monosodium adduct at m/z: 1051.75; theoretical m/z value: 1051.76); the C 16 chain might come from the degradation of an a-alkyl b-ketoacyl chain linked to trehalose by intramolecular retro-Claisen reaction as described previously (Puzo et al, 1979). The minor radiolabeled spots are not linked to the condensation activity.…”
Section: Chemistry and Biologymentioning
confidence: 99%
“…The major TDCM (22, Figure 15) contains a C32 corynomycolic acid, however, TDCMs with shorter acid chains (C24-C30) have also been found in Corynebacteria. TDCMs were first isolated in 1963, 77 and later found to be a mixture 78,79 which were separable once converted to their trimethylsilyl derivatives. 78 In more recent years, the isolation, and characterisation of TDCM (22) and mono-corynomycolate from…”
Section: 53a Introductionmentioning
confidence: 99%